Apply the distributive property to create an equivalent expression.
4\left(3 + \dfrac14c - \dfrac12d\right) =4(3+
4
1

c−
2
1

d)=

Respuesta :

Answer:

[tex]12+c-2d[/tex]

Step-by-step explanation:

The correct expression of the problem is

[tex]4\left(3 + \dfrac14c - \dfrac12d\right)[/tex]

Applying the distributive property

[tex]4\left(3 + \dfrac14c - \dfrac12d\right)=(4*3)+(4*\dfrac{1}{4} c)-(4*\dfrac{1}{2} d)=(12)+(c)-(2d)[/tex]

therefore

The equivalent expression is equal to

[tex]12+c-2d[/tex]